Presence of Rotavirus and free-living amoebae in the water supplies of Karachi, Pakistan - Yousuf, Farzana Abubakar; Siddiqui, Ruqaiyyah Bano *; Khan, Naveed Ahmed * (Universidade de Sao Paulo, 2017)
Rotavirus and pathogenic free-living amoebae are important health problem, especially for developing countries like Pakistan where public has limited access to clean water supplies. Here, we evaluated the prevalence of Rotavirus and free-living amoebae (Acanthamoeba spp., Balamuthia mandrillaris, Naegleria fowleri) in drinking water supplies to Karachi, Pakistan. Six water filtration plants that supply drinking water to the population of Karachi were investigated. Additionally, drinking water samples from households were analyzed for the presence of Rotavirus and free-living amoebae. Rotavirus was present in 35% of the water 26 samples collected from water filtration plants; however domestic tap water samples had a prevalence of only 5%. Out of 20 water samples from filtration plants, 13 (65%) were positive for Acanthamoeba spp., and one (5%) was positive for B. mandrillaris. Out of 20 drinking water samples collected from different areas of Karachi, 35% were found to be positive for Acanthamoeba spp. Rotavirus was detected in 5% of drinking water samples tested. Overall, these findings for the first time showed the presence of Rotavirus, in addition to pathogenic free-living amoebae in drinking water supplies in Karachi that could be an important public health risk for the affected population.